A Robust Blockchain-Based Distribution Master For Distributing Root Zone Data In DNS. (21st October 2022) - Liu, Yan; Yu, Haisheng; Wang, Wenyong; Zou, Sai; Liu, Dong; Gong, Daobiao; Li, Zhen
Abstract: Domain Name System (DNS) is a key infrastructure on the Internet. The Distribution Master (DM) system is used to transmit root zone data from Internet Assigned Numbers Authority (IANA) to the root server. DM is a centralized system that will introduce single points of failure and abuse of authority. To solve the problem of a single point of failure, we adopt the decentralization of blockchain in architecture, and propose a blockchain-based distributed DM architecture, which allows nodes to join and exit at any time. At the technical level, the 3R-PBFT (Replicated, Redundant Practical Byzantine Fault Tolerance) algorithm is proposed to reach a consensus, which increases the security of the system. We use flexible mechanisms to reduce the number of signatures and improve the performance of the system. A threshold signature algorithm is used to ensure the uniqueness of the signature key information, and the increase of DM nodes will not bring about an increase in the number of keys. The advantages of the system structure in stability and scalability were verified by experiments.